PENGARUH IDENTITAS GLOBAL, NILAI KEUNTUNGAN DAN NIAT BELI KAIN TENUN NTT - Daeng, Wendelinus Retas (AKSIOMA : Jurnal Manajemen, 2022)
The factors that determine a person to buy Ikat Flores- NTT woven fabrics are global identity, perceived functional value, perceived individual value, perceived social value and purchase intention. Flores Ikat Tenun- NTT is one of the woven fabrics that is popular with tourists when visiting the Flores area to be used as souvenirs. Therefore, the researcher wanted to find out whether global identity, perceived functional value, perceived individual value, and perceived social value can have an implication for purchase intention in Flores ikat fabric products. The quantitative method is the method used in conducting the analysis of this research, as well as collecting data by distributing questionnaires to 140 respondents consisting of men/women who have an age range of 23-39 years, have the intention to buy Flores ikat cloth products, and are tourists who come from Jabodetabek. In this study, researchers used the structural equation model (SEM) method with the help LISREL version 8.8. The results of this study prove that there is a positive relationship between global identity and perceived functional value on purchase intention. In this study it was also found that perceived individual value and perceived social value had no effect on purchase intention.
Keywords: woven fabrics; kain tenun ikat; global identity; purchase intention